Development and performance of self-sealed MRPC - Lyu, P.; Herrmann, Norbert; Deppner, Ingo Martin; Simon, Christian; Weidenkaff, Philipp (Journal of Instrumentation, 2017)
The MRPC has been widely applied in the high-energy physics experiments in recent decades for its excellent timing performance and good efficiency. The Compressed Baryonic Matter (CBM) experiment at FAIR plans to build its TOF system based on the MRPCs, aiming at a good hadron identification. The CBM-TOF will work at a very high particle flux rate ( 30 kHz/cm 2 ) condition, and the long-time exposure to such high-rate ionizing radiation will lead to severe gas aging problem on the MRPC. In order to improve the gas interchange inside the MRPC, we designed a new structure of self-sealed MRPC. It has a much smaller gas volume, which may accelerate the exchange process between the fresh and the polluted gas. The preparation time before the MRPC could work is also largely shortened. A prototype of self-sealed MRPC was produced in Tsinghua University, and it was tested in the CERN SPS Nov 2015 beam test organized by the CBM-TOF group. It showed around 98% efficiency and 60 ps time resolution. Due to the rate limit of 10 kHz/cm 2 in this beam test, we cannot make judgement on its performance under extremely high rate. Therefore further studies have to be performed under higher rate in order to study the capability of improving the gas exchange speed of this more flexible and operable sealed MRPC. This will allow that MRPC to be better suited for the high rate environment of TOF system while operating in the experiment.
Gesehen am 05.07.2018
14th Topical Seminar on Innovative Particle and Radiation Detectors (IPRD16)